Steel Bubbles: Death, Inexhaustibility, and Dickens’s Idea of the Book in Sketches by Boz, First Series (1836) - Jeffrey Jackson (Cahiers Victoriens et Edouardiens)
Sketches by Boz has been regarded as the book that qualified Charles Dickens as being among those paragons celebrated at Mrs Leo Hunter’s déjeuner in The Pickwick Papers: ‘real authors who had written whole books’. As a republishing of essays and short fiction in volume form, Sketches provides a locus classicus for book-history studies. Critics have shown little interest, however, in the originary volume of Sketches’s debut as a ‘whole book’, the two-volume edition of 1836, otherwise known as the First Series: most scholarly treatments take for their copy-text the 1839 edition. This essay reads the First Series in dialectic with the 1839 edition to discuss Dickens’s ambivalence toward ideas of authorship embodied in the material book. Where the 1839 Sketches uses death as an emblem of aesthetic fixity, the First Series celebrates inexhaustibility. Rather than suggesting a return to some pure, unmediated encounter with Dickens’s work, I emphasize textual materiality as a variable that has shaped receptions of both editions of Sketches and read the First Series to show how it, paradoxically, relies on the technology of the book to resist a sense of bookish closure.